Sport Values in Traditional Games as Playing Activities for Children - Iwandana, Dody Tri; Falaahudin, Ardhika; Nugroho, Wildan Alfia (Prodi PGSD Penjas FPOK UPI, 2021)
The purpose of this study was to determine the sport values in traditional games as playing activities for children. The natural activity of children is playing. The games that children play include team games and individual games. This research is a qualitative research employing a phenomenological approach method. The technique of selecting informants in this study used the Snowball Sampling technique. The subjects of this research were children, parents, and community leaders in Banjarnegara Regency understanding and knowing information about traditional games. Data collection techniques of this study consisted of observation, interview, and document analysis techniques. The data validity test used triangulation technique. Data analysis involved 4 stages, namely data collection, data reduction, data presentation, and conclusion drawing. The research results identified the sport valuescontained in traditional games, including cooperation, sportsmanship, honesty, struggling power, how to achieve victory, accept a defeat, self-esteem, trust, and self-confidence. Besides having positive impacts for health, traditional games can also train children to socialize with the surrounding community, know how to tolerate, help each other, and work together. Traditional games that can be found in Banjarnegara included mandahan, ular naga, marbles, engklekan, congklak, jumping rope, cublak-cublak suweng, stilts, jamuran, bentengan, and gobak sodor.